(untitled) (Research, Society and Development, 2020)
Introduction: The stretch mark consists of an cutaneous atrophy acquired, of a linear character, which may be in greater numbers or not, it is a condition that greatly affects pregnant women that produces significant emotional impact. Objective: To characterize the etiopathogenesis of stretch marks and to compare the mechanical and hormonal theory with the genetic influence. Methodology: This is a descriptive study and quantitative approach. The data collection was performed at the Basic Family Health Unit located in the city of Lagoa Seca. The sample is a postpartum patient who is under follow-up of nursing in the unit. Results and Discussion: About the heredograms generated, it is possible to observe the prevalence of individuals affected by stretch marks in most cases in the first and second generation. Another interesting finding is that the characteristic appeared at a given moment appears frequently in a given group, in another it appears with scarcity. 80% of the patients interviewed pointed out that their stretch marks are assimilated with that of a family member and only 20% reported a different location. Final considerations: It’s possible to infer that the development stretch mark can be associated due to single characteristics of the genotype or not, it was possible to recognize the role of heredity as an etiological factor in the present sampling.